Difference Is Not Indifference: Cicero and Modern Japan - Yasunari Takada (Ciceroniana On Line, 2020)
As Warsaw celebrated the 30th anniversary of its liberation from the totalitarian regime by reinvoking the Ciceronian tradition of republican ideal government, Japan found itself in a celebratory mood for the succession of imperial dynasty. Emperor Hirohito (d.1989)’s son was to be replaced by his grandson and thus Japan’s modern invention of an old tradition was to be consolidated. If European modernity has its origins in Renaissance and Reformation (i.e., critical renovation of the past both Classical and Christian) against the backdrop of the benighted Middle Ages, Japan’s modernity, ultimately a result of the emergency measure it took against the great wave of colonization by the west, cannot but be a composite of disparate ingredients. Whereas quick Westernization was prerequisite, equally indispensable was the spiritual consolidation of national identity. And herein comes the idea of renovating the ancient emperorship in a modern mold of absolute monarchy by singling out Shintoism for a kind of national religion: under such circumstances, the doom of Cicero’s reception needs no explanation. But this does not entirely exclude the possibility that an intellectual perspective characteristic of Japanese modernity can contribute to a better understanding of Cicero: where Cicero has been alienated, as indeed he still is, in the main stream of philosophy, the so-called European tradition of metaphysics, Japanese modernity with its inveterate polytheistic background of non-metaphysics has a chance to intervene for hermeneutic negotiations.